Pengaruh Profitabilitas, Solvabilitas, dan Inflasi terhadap Nilai Perusahaan - Yuli Tazkia Vidi; Yanuar Ramadhan (Reslaj : Religion Education Social Laa Roiba Journal, 2023)
Companies with positive corporate value trends are definitely attractive to investors. This is because a high company value indicates the level of prosperity of shareholders. Many things can affect the value of the company. This study aims to determine whether profitability, solvency, and inflation affect firm value. In this study there were 84 property and real estate industry populations listed on the Indonesia Stock Exchange from 2019 to 2021, and from the mixed sample results, 60 sample data were obtained. The analytical method used is multiple linear regression. The results of this study indicate that firm value is simultaneously influenced by profitability, solvency and inflation. Profitability has a positive and significant effect on firm value while solvency and inflation partially have no effect on firm value. Keywords: Firm Value; Profitability; Solvency; Inflation